Prevalence of Metabolic Syndrome: Association with Risk Factors and Cardiovascular Complications in an Urban Population - Moreira, Gisela Cipullo; Cipullo, José Paulo; Ciorlia, Luiz Alberto Souza; Cesarino, Cláudia Bernardi; Vilela-Martin, José Fernando (PloS one, 2014)
Metabolic syndrome (MS) is a set of cardiovascular risk factors and type 2 diabetes, responsible for a 2.5-fold increased cardiovascular mortality and a 5-fold higher risk of developing diabetes. 1-to evaluate the prevalence of MS in individuals over 18 years associated with age, gender, socioeconomic status, educational levels, body mass index (BMI), HOMA index and physical activity; moreover, to compare it to other studies; 2-to compare the prevalence of elevated blood pressure (BP), high triglycerides and plasma glucose levels, low HDL cholesterol and high waist circumference among individuals with MS also according to gender; 3-to determine the number of risk factors in subjects with MS and prevalence of complications in individuals with and without MS aged over 40 years. A cross-sectional study of 1369 Individuals, 667 males (48.7%) and 702 females (51.3%) was considered to evaluate the prevalence of MS and associated factors in the population. The study showed that 22.7% (95% CI: 19.4% to 26.0%) of the population has MS, which increases with age, higher BMI and sedentary lifestyle. There was no significant difference between genders until age ≥70 years and social classes. Higher prevalence of MS was observed in lower educational levels and higher prevalence of HOMA positive among individuals with MS. The most prevalent risk factors were elevated blood pressure (85%), low HDL cholesterol (83.1%) and increased waist circumference (82.5%). The prevalence of elevated BP, low HDL cholesterol and plasma glucose levels did not show significant difference between genders. Individuals with MS had higher risk of cardiovascular complications over 40 years. The prevalence of MS found is similar to that in developed countries, being influenced by age, body mass index, educational levels, physical activity, and leading to a higher prevalence of cardiovascular complications after the 4th decade of life.